Percutaneous Pedicle-Lengthening Osteotomy in Minimal Invasive Spinal Surgery to Treat Degenerative Lumbar Spinal Stenosis: A Single-Center Preliminary Experience - Maugeri, Rosario; Basile, Luigi; Gulì, Carlo; Banco, Aurelia; Giordano, Giovanna; Giugno, Antonella; Graziano, Francesca; Giammalva, Roberto Giuseppe; Iacopino, Domenico Gerardo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Lumbar spinal stenosis (LSS) is a narrowing of the spinal canal due to spinal degeneration, and its main clinical symptom is neurogenic claudication. Surgical treatment is pursued for patients who do not improve with conservative care. Patients with symptomatic LSS who also have significant medical comorbidities, although clearly in need of intervention, are unattractive candidates for traditional open lumbar decompressive procedures. Thus it is important to explore minimally invasive surgical techniques to treat select patients with LSS.Methods This retrospective case series evaluated the clinical and radiographic outcomes of a new minimally invasive procedure to treat LSS: pedicle-lengthening osteotomy using the ALTUM system ((Innovative Surgical Designs, Inc., Bloomington, Indiana, United States). Peri- and postoperative demographic and radiographic data were collected from a clinical series of seven patients with moderate LSS who were > 60 years of age. Clinical outcome was evaluated using visual analog scale (VAS) scores and the spinal canal area on computed tomography scans.Results Twelve months after the procedure, scoring revealed a median improvement of 3.7 on the VAS for the back and 6.3 on the VAS for the leg, compared with the preoperative baseline (p < 0.05). The postoperative central area of the lumbar canal was significantly increased, by 0.39 cm2; the right and left neural foramina were enlarged by 0.29 cm2 and 0.47 cm2, respectively (p < 0.05).Conclusions In this preliminary study, the ALTUM system showed a good clinical and radiologic outcome 1 year after surgery. In an older or high-risk population, a short minimally invasive procedure may be beneficial for treating LSS.
Keywords: lumbar spinal stenosis; pedicle-lengthening osteotomy; minimal invasive spinal surgery; lumbar degenerative disease